Factors associated with procedural difficulty and major adverse events during transcatheter closure of the patent ductus arteriosus - Araya Tipsungnoen; Jirayut Jarutach; Supaporn Roymanee; Kanjarut Wongwaitaweewong; Rujira Buntharikpornpun; Suppalak Puttarak; Kemmapon Chumchuen (PLoS ONE, 2026)
Transcatheter closure of the patent ductus arteriosus (PDA) is widely accepted as an alternative to surgical ligation. However, major complications are uncommon. Therefore, procedural difficulty, including device repositioning or change, may provide additional insight into technical challenges encountered during PDA closure. We aimed to identify the clinical and anatomical risk factors associated with procedural difficulty or major adverse events during transcatheter PDA closure and to document the prevalence and types of complications encountered in a single tertiary center. This retrospective cohort study included 341 patients who underwent a transcatheter PDA closure between 2010 and 2023. A composite primary outcome, defined as procedural difficulty or major adverse events, included device malposition requiring reposition or change, unsuccessful device deployment, device embolization, hemodynamic instability requiring intervention, or unplanned surgical conversion. Demographic, anatomical, and hemodynamic variables were analyzed. Univariate and multivariate logistic regression analyses were performed to identify independent predictors. Procedural difficulty or major adverse events occurred in 49 patients (14.3%). There was no procedure-related mortality. Device embolization occurred in three patients (0.8%), all requiring surgical ligation. Multivariate analysis revealed that a minimum PDA diameter >5 mm (odds ratio [OR] = 2.75, P = 0.013), PDA length >8 mm (OR = 2.81, P = 0.009), and non-type A (non-conical) duct morphology (OR = 2.88, P = 0.025) were independently associated with the composite outcome. In conclusion, larger PDA diameter, longer ductal length, and non-conical morphology were significantly associated with increased procedural difficulty or major adverse events during transcatheter PDA closure. These findings highlight the importance of detailed anatomical assessment in patients undergoing transcatheter PDA closure.